2017
DOI: 10.1242/jcs.199760
|View full text |Cite
|
Sign up to set email alerts
|

Transient mechanical strain promotes the maturation of invadopodia and enhances cancer cell invasion in vitro

Abstract: Cancer cell invasion is influenced by various biomechanical forces found within the microenvironment. We have previously found that invasion is enhanced in fibrosarcoma cells when transient mechanical stimulation is applied within an in vitro mechano-invasion assay. This enhancement of invasion is dependent on cofilin (CFL1), a known regulator of invadopodia maturation. Invadopodia are actin-rich structures present in invasive cancer cells that are enzymatically active and degrade the surrounding extracellular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 86 publications
(103 reference statements)
3
45
0
Order By: Relevance
“…Invadopodia use MMP2, MMP9, and MT1-MMP to degrade the BM ( Clark et al, 2007 ; Poincloux et al, 2009 ). Application of mechanical strain onto the surrounding ECM enhances invadopodia maturation and cell invasion ( Gasparski et al, 2017 ). Invadopodia activity is highest at moderate levels of cross-linking in collagen I matrices, compared with much lower or higher cross-linking ( Pourfarhangi et al, 2018 ).…”
Section: Chemical and Physical Modes Of Bm Invasionmentioning
confidence: 99%
“…Invadopodia use MMP2, MMP9, and MT1-MMP to degrade the BM ( Clark et al, 2007 ; Poincloux et al, 2009 ). Application of mechanical strain onto the surrounding ECM enhances invadopodia maturation and cell invasion ( Gasparski et al, 2017 ). Invadopodia activity is highest at moderate levels of cross-linking in collagen I matrices, compared with much lower or higher cross-linking ( Pourfarhangi et al, 2018 ).…”
Section: Chemical and Physical Modes Of Bm Invasionmentioning
confidence: 99%
“…Transient mechanical strain facilitates maturation of invadopodia, elongation of invadopodia and subsequently a pronounced migration and invasion of cells into hydrogels due to this mechanical load (Menon and Beningo, 2011;Gasparski et al, 2017). Hence, enhanced invasion due to this mechanical stimulus necessitates the cells to be invasive by themselves, since non-invasive cells cannot be induced to be invasive.…”
Section: Transient Mechanical Strain Affects Highly Invasive Cellsmentioning
confidence: 99%
“…As a consequence of encouraging maturation of invadopodia, there is a concomitant enhancement of MMP activity levels linked to invadopodia. Tugging forces have been established as intrinsically supportive of metastatic cell invasion, and they continue to deliver a mechanical stimulus for the foundation of mechanically initiated maturation of invadopodia (Gasparski et al, 2017).…”
Section: Transient Mechanical Strain Affects Highly Invasive Cellsmentioning
confidence: 99%
“…In vitro experiments have shown that change in stiffness can alter cell proliferation, even promote cancer growth. Adding to the mechanical property of cells, including the cancer cells, the tumor stiffness itself is promoting tumor growth 20 . Ideas have begun to emerge that tumor growth might be affected when the sensory proteins in the cancer cells were inhibited.…”
Section: Mechanical Properties In 2d and 3d Cell Modelmentioning
confidence: 99%